2003
DOI: 10.1007/s11745-003-1069-x
|View full text |Cite
|
Sign up to set email alerts
|

n−3 long‐chain FA decrease serum levels of TG and remnant‐like particle‐cholesterol in humans

Abstract: A large number of papers have reported that administration of n-3 FA reduced serum TG concentrations in hypertriglyceridemic patients. However, few studies have examined the effect of n-3 FA on serum concentrations of remnant-like particle (RLP) cholesterol. Volunteers (n = 41) whose serum TG concentrations were 100-300 mg/dL were recruited and randomly assigned to either an n-3 FA group or a control group with stratification by sex, age, and serum TG level in a double-blind manner. The subjects in the n-3 FA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
3
23
3
1
Order By: Relevance
“…The reasons why there were no significant differences in those lipid levels between the EPA and control groups were not clear. However, the mean basal levels in subjects in the previous study (15) were rather high (triglycerides: 1.65-1.83 mmol/L; RLP-cholesterol: 0.13-0.15 mmol/L) compared with the present study (see Table 7). This might be one of the reasons.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The reasons why there were no significant differences in those lipid levels between the EPA and control groups were not clear. However, the mean basal levels in subjects in the previous study (15) were rather high (triglycerides: 1.65-1.83 mmol/L; RLP-cholesterol: 0.13-0.15 mmol/L) compared with the present study (see Table 7). This might be one of the reasons.…”
Section: Discussioncontrasting
confidence: 83%
“…Recently we reported that the test food reduced the serum levels of triglycerides and RLP-cholesterol (15). The reasons why there were no significant differences in those lipid levels between the EPA and control groups were not clear.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the AHA recommends 3-4 g/day of long chain omega-3 fatty acids for the treatment of hypertriglyceridemia [7] and studies suggest that use of fish oils may also substantially reduce Remnant-Like Particle cholesterol [RLP-cholesterol] a novel cardiovascular disease risk factor [18][19][20]. However, the generally accepted safety limit for consumption of EPA and/or DHA is 3 g/day [6,7], which imposes a constraint on the adoption of this treatment recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…Hamasaki et al [195] reported that n-3 long-chain FA decreased serum TG and RLP-C in humans. The effect of EPA on serum RLP-C was assessed in 10 patients with noninsulin-dependent diabetes.…”
Section: Fibrates Significantly Decrease Plasma Apob48 and Remnant LImentioning
confidence: 99%
“…It is believed that omega-3 fatty acids enhanced CM clearance via reduced hepatic VLDL synthesis [194]. Moreover, in experimental models, omega-3 fatty acids may also reduce intestinal lipoprotein production [195], which is increased in insulin resistance [168] and type 2 diabetes [196]. These preliminary findings suggested that supplementation with omega-3 fatty acids (4 g) to higher dose fluvastatin in diabetics with mixed hyperlipidemia was accompanied by a significant additional benefit in apoB-48 containing particles.…”
Section: Fibrates Significantly Decrease Plasma Apob48 and Remnant LImentioning
confidence: 99%